2019
DOI: 10.4103/ijpvm.ijpvm_310_17
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle hypertrophy, insulin-like growth factor 1, myostatin and follistatin in healthy and sarcopenic elderly men: The effect of whole-body resistance training

Abstract: Background:Sarcopenia describes the inevitable deterioration in muscle mass and strength that accompanies biological aging. The purpose of this study was to investigate the effects of resistance training (RT) on quadriceps hypertrophy and related biochemistry in sarcopenic and healthy elderly men.Methods:A total of 31 elderly men (55–70 years old) were classified as sarcopenic and nonsarcopenic and were divided into two groups. Both groups participated in a progressive RT program for 8 weeks.Results:Data indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…In the present study, a significantly positive relationship was seen between the expression of myostatin gene and the insulin resistance in diabetic rats, and decreased expression of myostatin gene was associated to improved insulin resistance. These findings were similar to findings from other studies that reported high levels of myostatin in diabetic (35,36), obese (11,37) and elder (23) patients (associated with metabolic-cardiovascular risk factors such as insulin resistance). Hitle et al (2010) reported that both muscle and plasma myostatins decreased by aerobic exercises and this decrease was linked to improvement of insulin resistance in diabetic participants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, a significantly positive relationship was seen between the expression of myostatin gene and the insulin resistance in diabetic rats, and decreased expression of myostatin gene was associated to improved insulin resistance. These findings were similar to findings from other studies that reported high levels of myostatin in diabetic (35,36), obese (11,37) and elder (23) patients (associated with metabolic-cardiovascular risk factors such as insulin resistance). Hitle et al (2010) reported that both muscle and plasma myostatins decreased by aerobic exercises and this decrease was linked to improvement of insulin resistance in diabetic participants.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Jensky et al (2010) showed that seven sessions of extreme extrinsic resistance training with one leg and introversion one as open chain knee isokinetic movements included no effects on myostatin mRNA levels in young women (22). In contrast, Negaresh et al (2019) investigated effects of whole-body resistance training in healthy elderly people and patients with sarcopenia and showed that resistance training decreased myostatin in both groups (23). Willoughby (2004) demonstrated that heavy resistance training in healthy individuals for 12 weeks was associated to increased expression of mRNA and myostatin protein (24).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TGF-β1 is known as a multifunctional protein that acts as a skeletal muscle regenerator since it contributes to extracellular matrix reconstitution as well as muscle tissue remodelling (33) . Several investigations have evaluated the aforementioned myokines to determine their role in RT-induced muscular adaptations (1,30,34,35) . Accordingly, we showed that 8 weeks of wholebody RT increased circulating FLST and decreased MSTN concentrations in middle-aged men (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of novel research studies have been focused on the relationship between serum myostatin and muscle mass and function, and thus, its potential as a biomarker, the results seem unclear. Most studies indicate that a higher circulating myostatin concentration can be found in patients with higher muscle mass [ 79 , 80 , 81 , 82 , 83 , 84 , 85 ], but a few research studies resulted in finding such an association only in men [ 86 , 87 ], and some did not show any correlation with muscle mass parameters at all [ 88 , 89 , 90 , 91 ]. A study on healthy, obese and metabolically unhealthy participants found a contradictory, significantly negative correlation between muscle mass and serum myostatin, suggesting a major influence of metabolic syndrome on circulating myostatin level [ 92 ].…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%